How does organisational capacity contribute to advocacy effectiveness? Taking stock of existing evidence. Issue 5 (3rd July 2020) - Elbers, Willem; Kamstra, Jelmer
ABSTRACT: Despite a growing interest in advocacy for marginalised groups within international development, the relationship between organisational capacity and advocacy effectiveness is not yet fully understood. This article synthesises existing empirical research on advocacy for marginalised groups in the Global South. It presents a framework that identifies the main enabling factors for advocacy effectiveness and the organisational capacities and requirements associated with these. The article disentangles the abstract notion of advocacy capacity into concrete components, with eight core advocacy capacities identified: the capacity to (1) produce evidence, (2) inspire trust among power holders, (3) represent constituency interests, (4) analyse the political arena, (5) produce tailored messages, (6) work collectively, (7) build rapport with power holders, and (8) adapt to ongoing changes in the environment. Finally, the article reflects on the promises and pitfalls of using the capacity framework in real-world settings.